YARGITAY KARARLARI KAPSAMINDA İMARA AYKIRI YAPILARDA TESCİL VE TAZMİNAT TALEPLERİ - (:unkn) unknown (My University, 2016)
Bir inşaata ruhsat alınmadan başlanmışsa veya inşaat ruhsata aykırı şekilde tamamlanmamışsa imar kurallarına aykırı bir inşaatın yani kaçak inşaatın varlığı söz konusu olur. Bu aykırılık sonucu oluşan ifa imkânsızlığının geçici veya sürekli olmasına göre bağımsız bölüm alan alıcıların, arsa sahiplerinin tescil ve tazminat talepleri, inşaatı yapan müteahhidin ücret talebi uygulamada çok sayıda uyuşmazlığa konu olmakta ve Yargıtay tarafından da farklı ihtimallere göre taraf menfaatlerini etkileyecek önemli ve emsal oluşturacak kararlar verilmektedir. Ruhsata aykırı ve kaçak kabul edilebilecek bir yapıya taşkın yapı, kazı fiilleriyle zarar verilmesi de yine tazminat taleplerine konu edilmekte ve Yargıtay'ın emsal nitelikli kararlarına esas oluşturmaktadır.

An illegal building, a building that contradicts the zoning rules, comes to subject in case a construction is started without a construction license or if the construction is completed violating the construction license. In practical, depending on whether the legal impossibility which arises from this contradiction is temporary or permanent, land registration and compensation demands of building purchasers and owners, the demand of charges of the contractors engaged in construction becomes the subject of numerous disputes and the Yargıtay gives important and precedent decisions based on different possibilities that will affect the interests of parties. Illegal excavation to damage an illegal building that violates the license is again subject to claim and constitutes a basis for precedent qualified decisions of the Yargıtay.
Rehistration Request and Claim For Damages For Constructions Against The Reconstruction Permit Within The Scope of Supreme Court Decisions
Keywords: Hukuk